Binary hydrocarbon mixtures of Joule-Thomson refrigeration cycle based for -70 C freezer: Theoretical and experimental evaluation - Lingeng Zou; Tao Bai; Shuo Guo; Jianlin Yu (Case Studies in Thermal Engineering)
Recently, with the increasing worldwide demand for low-temperature freezers, applying natural working medium hydrocarbon refrigerants has been widely concerned. For obtaining a −70 °C freezer, the Joule-Thomson refrigeration cycle of two kinds of binary hydrocarbon mixtures, R1150/R600 and R170/R600, were analyzed and experimentally verified. The theoretical analyses results indicated that the thermodynamic performance of R1150/R600 mixed refrigerant was better than that of R170/R600 when it was used in Joule-Thomson refrigeration system of −70 °C freezer. The coefficient of performance (COP) and the volume cooling capacity of using R1150/R600 was improved by 37.9 % and 50.7 %, respectively, compared with that of R170/R600. For further verify the results of theoretical analysis, two kinds of mixed refrigerants were tested with a low-temperature freezer prototype. The experimental results demonstrate that the lowest cabinet temperature that R170/R600 could reach was −66.9 °C at an ambient temperature of 32 °C with a refrigerant charge of 150g. On the other hand, when the concentration of R1150 is 27.5 %, the average temperature in the cabinet could reach −72 °C, indicating that the application of R1150/R600 in a low-temperature freezer at −70 °C has great potential. In summary, under the existing system configuration, the R1150/R600 was more suitable for −70 °C freezer than the R170/R600. This study could provide theoretical and experimental guidance for the selection of refrigerants for low-temperature freezers based on the Joule-Thomson refrigeration system.